MASS PUBLIC TRANSPORTATION SYSTEM POLICY IN THE MILLENNIUM ERA IN INDONESIA - Leo Barus (Scientia Integritas Utama, 2022)
The Millennium Era at the beginning of 2050 left challenges that every country, including Indonesia, must handle early. Indonesia, which currently has around 273.88 million, will impact the transportation system. Based on a literature study, it is concluded that the policy for the availability of an ideal mass public transportation system in the millennium era in Indonesia must be problem-oriented and integrated forecasting with monitoring and evaluation of policies continuously over time. The policy recommendation is the provision of environmentally friendly bus transportation, such as electric buses, and improving facilities, safety and comfort. Considering a large number of motorcycles and passenger cars in Indonesia, there is a need for a policy that is based on normative juridicalism on the rate of passenger cars and motorcycles using fossil fuels by 2050, including by imposing a carbon tax.